The analysis of mathematics performance and learning problems of pre-engineering students - Ahmad Shariff, A. (2013)
The focus of this research is to analyze and study the mathematics performance of 185 pre-Engineering students in Center for Foundation Studies in Science (CFS), University of Malaya, based on their achievements in the Malaysian Certificate of Education (MCE) Additional Mathematics (AM). Students with A1 and A2 (Group A) for the MCE AM subject can be considered as good students while those getting B3, B4 and C5 (Group B) are less performed ones. This study shows that the students’ performances in Mathematics were influenced significantly by their AM achievements. Linear regression analysis conducted on AM results and the results of Mathematics paper; generally found that students who excel in Mathematics were students from Group A. However, there are also students from Group A who did not achieve good results in CFS Mathematics. Other than that, almost 100% of the students from Group B failed in the Mathematics subject in CFS. Further study conducted is to identify the ‘outliers’ category students under the regression lines whereby the questionnaire was carried out on them to study the actual problems they faced whether the problem was caused by learning systems or teaching staffs in CFS as well as environmental problems or personal problems.